2016
DOI: 10.1039/c6ra09013c
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked polymeric self-assemblies as an efficient strategy for photodynamic therapy on a 3D cell culture

Abstract: Polymeric crosslinked self-assemblies based on poly(ethyleneoxide-b-ε-caprolactone) have been synthesized. They are shown to be more efficient vectors for photodynamic therapy compared to uncrosslinked systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…plates, hanging drop methods etc.) where they assume naturally a spherical aggregate conformation [67][68][69] or by embedding cells in a 3D matrix. The closely packed arrangement where cell to cell contact is dominant and the reduced rate of diffusion of drugs and oxygen through the spheroids makes them comparable to in vivo tissues.…”
Section: Spheroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…plates, hanging drop methods etc.) where they assume naturally a spherical aggregate conformation [67][68][69] or by embedding cells in a 3D matrix. The closely packed arrangement where cell to cell contact is dominant and the reduced rate of diffusion of drugs and oxygen through the spheroids makes them comparable to in vivo tissues.…”
Section: Spheroidsmentioning
confidence: 99%
“…129 Yang et al (2015) 121 also observed a more homogenous response where the dead cells were found to be distributed across the full thickness of the cancer tissue in the 3D model post-treatment with 5-ALA and AuNPs combined, whereas with 5-ALA-only PDT, a majority of the dead cells were identified within the superficial parts of the cancer tissue. Till et al (2016) 68 on the other hand used 3D spheroid models developed from human colorectal carcinoma cell line (HCT-116) and human squamous cell carcinoma cell line (FaDu) on ultra-low attachment plates for investigating PDT efficacy. This study compared PDT using a pheophorbide photosensitiser (Pheo) in free solution form to the use of encapsulated photosensitiser in crosslinked polymeric micellar self-assemblies versus uncrosslinked micellar counterparts.…”
Section: The Use Of Nanoparticles In Pdt and Their Applications In 3dmentioning
confidence: 99%
“…The most frequently suggested solution to avoid any dissociation upon dilution is cross-linking of the vector. For PDT and other therapeutic cases this has been also described [66], showing a strong improvement of the treatment. The PS can be used both as ROS generator and also as cross-linker [101].…”
Section: Vector Stabilitymentioning
confidence: 80%
“…PIC with PS HUVEC and lung carcinoma, in vitro [46,47] poly(ethylene oxide)-block-poly(α,β-aspartic acid)/poly([5-aminopentyl]-α,β-aspartamide) -lung carcinoma, in vitro [48] poly(ethylene oxide)-block-poly(α,β-aspartic acid) PIC with PS lung carcinoma, in vitro [49] poly(N-methyl-2-vinylpyridinium iodide)-block-poly(ethylene oxide) PIC with PS - [50,51] [64] poly(oligo(ethylene oxide)methyl ether methacrylate)-block-poly(ʟ-lysine) O 2 production image-guided (FI), liver and breast cancer, in vitro [65] methoxy-poly(ethylene oxide)-block-poly(ε-caprolactone)-benzyl degradation macrophages and endothelial cells, in vitro [40] poly(ethylene oxide)-block-poly(ε-caprolactone) degradation colon cancer and carcinoma, in vitro [37,66,67] poly(ethylene glycol)-block-poly(lactic acid) degradation [38] poly(ethylene glycol)-block-poly(ᴅ,ʟ-lactide-co-benzyl glycidyl ether) degradation macrophage and kidney cells, in vitro [45] poly(ethylene glycol)-block-poly(ε-caprolactone)-block- aliphatic polyesters, based for instance on ε-caprolactone or lactic acid [36][37][38][39][40][41]. In particular, the degradation of polyesters in vivo, a combination of both hydrolytic and enzymatic processes, makes them a first choice for the controlled delivery of drugs [42].…”
Section: Physical Solubilization Of the Photosensitizermentioning
confidence: 99%
See 1 more Smart Citation